Influence of cation Si 4+ ↔ Ge 4+ and P 5+ ↔ Ge 4+ substitution on the mechanical parameters of single crystals Ag7 (Si 1–x Ge x )S5I and Ag6+x (P1–x Gex )S5I - Shender Iryna; Шендер Ірина; Pogodin Artem; Погодін Артем; Filep Mykhailo; Філеп Михайло; Filep Mihály; Malakhovska Tetyana; Малаховська Тетяна; Oleksandr Kokhan; Кохан Олександр; Vitaliy Bilanych; et al. (My University, 2023)
Abstract. Herein we present the results of microhardness investigations aimed at monocrystalline samples of Ag7(Si1–xGex)S5I (0, 0.2, 0.4, 0.6, 0.8, 1) and Ag6+x(P1–xGex)S5I (0, 0.25, 0.5, 0.75, 1) solid solutions. The dependence of microhardness H on the load P and composition were investigated. It has been observed that the microhardness dependence on the applied load is characterized by a tendency to decrease with increasing the load. It indicates a presence of “normal” size effect in both Ag7(Si1–xGex)S5I and Ag6+x(P1–xGex)S5I (0, 0.25, 0.5, 0.75, 1) solid solutions. The revealed size effects of hardness in single crystals of Ag7(Si1–xGex)S5I and Ag6+x(P1-xGex)S5I solid solutions have been analyzed within the framework of the gradient theory of plasticity. The corresponding parameters of the model of geometrically necessary dislocations have been determined.

Резюме. У даній роботі наведено результати досліджень мікротвердості монокристалічних зразків твердих розчинів Ag7(Si1–xGex)S5I (0, 0.2, 0.4, 0.6, 0.8, 1) та Ag6+x(P1–xGex)S5I (0, 0.25, 0.5, 0.75, 1). З’ясовано залежність мікротвердості H від навантаження P та складу. Виявлено, що залежність мікротвердості від прикладеного навантаження характеризується тенденцією до зменшення зі збільшенням навантаження. Це свідчить про наявність прямого розмірного ефекту як у твердих розчинах Ag7(Si1–xGex)S5I, так і Ag6+x(P1–xGex)S5I. Виявлені розмірні ефекти зміни твердості у монокристалах твердих розчинів складу Ag7(Si1–xGex)S5I та Ag6+x(P1–xGex)S5I було проаналізовано в рамках градієнтної теорії пластичності. Визначено відповідні параметри моделі геометрично необхідних дислокацій.
Вплив катіонного Si 4+ ↔ Ge 4+ and P 5+ ↔ Ge 4+ заміщення на механічні параметри монокристалів Ag7 (Si 1–x Ge x )S5I та Ag6+x (P1–x Gex )S5I
Contents: http://journal-spqeo.org.ua/n4_2023/n4_2023_contents.htm Editorial board: http://journal-spqeo.org.ua/EditorialBoard.html
Keywords: argyrodite; single crystal; microhardness